The Nature of Urban Design: The Lessons of Experience - Lang, Jon (NAJUA: Architecture, Design and Built Environment, 2016)
Cities are constantly being designed, piece-by-piece, by thousands of individuals seeking to fulfill their own interests. They have to work within the laws of a land, to the extent that the laws are enforced. Individual actions may vary in scale from placing a flower box filled with petunias on a front stoop to the building of several blocks of the city. Inadvertent actions also shape the city. The stepping of feet erodes stairs and fingerprints mark walls. Ice creams are dropped on the ground and sidewalks are smeared with the residue of chewing gum (except in Singapore). Nature too is a designer; buildings decay, the rain stains buildings and abandoned sites fill with weeds. The city evolves. We have learnt much from the experiences of the past five decades.